Non-Synonymous Mutation Analysis of SARS-CoV-2 ORF3a in Indonesia - Hartiyowidi Yuliawuri; Jeanne Elvia Christian; Nathanael Steven (Molecular and Cellular Biomedical Sciences, 2022)
Background: The report of mutation sites ORF3a SARS CoV-2 in Indonesia is still limited. Some research showed that mutations in ORF3a protein might alter SARS-CoV-2 pathogenesis. Observation of new variants should be conducted as a risk monitoring framework.Materials and method: We assessed the impact of mutations in ORF3a protein by analyzing 3,751 SARS-CoV-2 DNA sequences from the GISAID database from March 2020 until July 2021. The whole-genome sequences were aligned using Clustal Omega Multiple Sequence Alignment from EMBL-EBI and analyzed using BioEdit version 7.2.5 software. The reference whole genome sequence was taken from the Genbank database with accession number NC045512. We excluded the samples containing N letters due to inaccurate reading. Effect of point mutations on protein structure was analyzed using PredictProtein (https://predictprotein.org) and Protein Variation Effect Analyzer (PROVEAN) v1.1.3. online software.Results: We identified five most frequent non-synonymous mutations in ORF3a protein of SARS-CoV-2 which were Q57H (58.04%), S26L (27.25%), S220I (10.37%), D155H (8.98%), and P104S (5.47%).Conclusion: These mutation data showed the phenomenon of amino acid changes in ORF3a SARS-CoV-2 in Indonesia until July 2021. The implication of this mutation needs to be determined in further studies.Keywords: Indonesia, mutations, non-synonymous, SARS-CoV-2, whole genome